Tensile And Impact Properties Of Cost-Effective Hybrid Fiber Metal Laminate Sandwich Structures - Dhar Malingam, Sivakumar; Ng, Lin Feng; Subramaniam, Kathiravan; Ab Ghani, Ahmad Fuad; Jumaat, Faizal Azli (John Wiley and Sons Inc., 2017)
Hybrid composite materials, which combine two or more types of fiber in a single matrix, have currently drawn the interest of researchers. This research investigates the tensile and impact properties of hybrid kenaf/glass reinforced metal laminates (FMLs) with different fiber orientations and stacking configurations. FMLs were formed by sandwiching the annealed aluminum 5052 sheets to the composite laminates using hot press molding compression technique. The tensile test was performed at a quasi-static rate of 2 mm/min with reference to ASTM E8 whereas Charpy impact test was conducted using impact pendulum tester according to ASTM E23. Results showed that improvement in tensile and impact strength was observed in hybrid FMLs compared to kenaf fiber reinforced FMLs. Fiber orientation of ±45° reduced the tensile strength but increased the impact strength of FMLs in comparison with fiber orientation of 0°/90°. Overall, hybrid FMLs incorporated with a fiber stacking sequence of glass/kenaf/glass showed superior characteristic in tensile and impact performance.